Determining Business Strategy of Inspection Companies in Oil and Gas Upstream Business Activities - Yogi Arie Wibowo; Anak Agung Bagus Dinariyana Dwi Putranta; Jerry Dwi Trijoyo Purnomo (IPTEK Journal of Proceedings Series, 2020)
Inspection companies supporting upstream oil and gas business activities with multi-owned businesses are demanded to compete and survive in increasingly fierce market competition. Differences in the characteristics and scope of each business unit makes the company encouraged to be more observant in seeing the position rate of development of each business unit. A strategy is needed to ensure the treatment of each of these business units in order to achieve company goals. Identification, clustering and analysis of influencing factors affecting the company business performance are carried out through the stages of collecting secondary and primary data to obtain a follow-up plan for each business unit of the company. We use the real case in one of Indonesian Inspection Company. The method used in this paper is the analysis of strategy formulation in determining business strategies by three stages. First stage IFE (Internal Factors Evaluation) matrix and EFE (External Factor Evaluation) matrix are prepared then follow by IE (Internal External Matrix). Second stage, by assesment the following matrixes, we matched up with SWOT (Strength, Weakness, Opportunity, and Threat) matrix. Finally the final stage is taken by using QSPM (Quantitative Strategic Planning Matrix) to determine reliable strategy for inspection company in the upstream oil and gas business activities.